What is the impact of recent reforms on English teaching in vocational education in Ningbo? - Wang, Wanyu (2020)
This thesis investigates the impact of recent curriculum reforms on English teachers and teaching in secondary vocational education in a Chinese city. It uses case study methodology to examine the impact of the reforms on teachers’ professional identities and the factors that support or challenge their professional development. The study draws upon Lave and Wenger’s theories about communities of practice to explain the pressures the teachers are under. The thesis contributes to a better understanding of how vocational English teachers’ professional identity is being reorganised within a transforming educational context, and it raises a demand for better comprehension of the relationship between individual and context in the implementation of educational reform in China.